2008
DOI: 10.1021/je800579j
|View full text |Cite
|
Sign up to set email alerts
|

Densities, Refractive Indices, and Excess Properties of Binary Mixtures of 1,4-Dioxane with Benzene, Toluene, o-Xylene, m-Xylene, p-Xylene, and Mesitylene at Temperatures from (288.15 to 318.15) K

Abstract: The densities (ρ) and refractive indices (n) of binary mixtures of 1,4-dioxane with benzene, toluene, o-xylene, m-xylene, p-xylene, and mesitylene, including those of pure liquids, over the entire composition range expressed by mole fraction x 1 of 1,4-dioxane were measured at temperatures (288.15, 293.15, 298.15, 303.15, 308.15, 313.15, and 318.15) K under atmospheric pressure. From the experimental data, the excess molar volumes (V m E), deviations in refractive indices (Δn), partial molar volumes (V m,1 °∞… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 33 publications
(44 reference statements)
4
17
0
1
Order By: Relevance
“…The increase in values with the increase in number of -CH 3 groups implies that dipole-induced dipole interaction is weaker in higher hydrocarbon owing to its decreased polarizabilities with the increase of -CH 3 groups. A similar type of study was reported by Nain et al [16] for 1,4-dioxane and hydrocarbons. The observed values are in the order of Benzene < Toluene < p-xylene < m-xylene < o-xylene < Mesitylene Addition of two methyl groups in benzene ring in xylenes further exceeds the electron donating capacity, when compared to toluene, but at the same time steric (hindrance) repulsion between methyl groups of 1-iodobutane which hinders proper orientation that is expected to be more.…”
Section: Resultssupporting
confidence: 76%
“…The increase in values with the increase in number of -CH 3 groups implies that dipole-induced dipole interaction is weaker in higher hydrocarbon owing to its decreased polarizabilities with the increase of -CH 3 groups. A similar type of study was reported by Nain et al [16] for 1,4-dioxane and hydrocarbons. The observed values are in the order of Benzene < Toluene < p-xylene < m-xylene < o-xylene < Mesitylene Addition of two methyl groups in benzene ring in xylenes further exceeds the electron donating capacity, when compared to toluene, but at the same time steric (hindrance) repulsion between methyl groups of 1-iodobutane which hinders proper orientation that is expected to be more.…”
Section: Resultssupporting
confidence: 76%
“…The comparison with the literature allowed us to determine a high reproducibility for benzene [28,29,30] and DMSO [31,26,32,33,27] (See Table 2). Additionally, the measurements at 657.7 nm were compared with those values of the literature deterined at the closed wavelength available, e.g.…”
Section: Methodological Detailsmentioning
confidence: 99%
“…Lit. [ref] THFA 298.15 1.04761 1.04761 [25] 4.89883 4.89883 [25] 1.4532 1.45322 [25] Benzene 298.15 0.87372 0.87357 [26] 0.87361 [27] 0.87360 [28] 0.87342 [29] 0.59951 0.6038 [26] 0.604 [28] 1.4975 1.4980 [27] 1.4971 [29] Toluene 298.15 0.86224 0.86301 [26] 0.86236 [27] 0.86220 [28] 0.86226 [29] 0.55464 0.5540 [26] 0.556 [28] 1.4950 1.4942 [27] 1.4931 [29] p-xylene 298.15 0.85676 0.85670 [26] 0.85682 [27] 0.85662 [28] 0.85670 [29] 0.61225 0.6078 [26] 0.611 [28] 1.4945 1.4933 [27] 1.4926 [29] Exp. : experimental, Lit.…”
Section: Measurementsunclassified